Endodontic treatment and esthetic management of a primary double tooth with direct composite using silicone buildup guide - Vinaya Kumar Kulkarni; T Raju Ragavendra; Jeevanand Deshmukh; Amit Vanka; Mahesh Kumar Duddu; Anand Kumar G Patil (Wolters Kluwer Medknow Publications, 2012)
Gemination and fusion are morphological dental anomalies, characterized by the formation of a clinically wide tooth. Gemination occurs when one tooth bud tries to divide, while fusion occurs if two buds unite. The terms double teeth, double formation, conjoined teeth, geminifusion, vicinifusion and dental twinning are often used to describe fusion and gemination. Double teeth are associated with clinical problems such as poor esthetics, spacing problems and caries susceptibility. Management of such cases requires a comprehensive knowledge of the clinical entity as well as the problems associated with it. This report presents a case of primary double tooth in a 6-year-old boy involving maxillary left central incisor. The anomalous tooth was carious and pulpally involved. This was treated conservatively by endodontic treatment and esthetic rehabilitation was done with direct composite restoration using a silicone buildup guide. The treated tooth was followed up until exfoliation.